FINANCIAL RATIO ANALYSIS TO ASSESS FINANCIAL PERFORMANCE AT PT PEGADAIAN (PERSERO) USING PROFITABILITY, LIQUIDITY AND SOLVENCY RATIOS FOR THE 2020-2024 PERIOD - Jason Nicholas Bonar Parulian Tampubolon; Jessica Dwi Yolanda Pandiangan; Iin Sri Ayu Sihotang; Diva Maulidia; Sabrina Salsabilah; R.Ayu. Fatimah; Firdha Dwi Yudha Lubis; Anggi Pratama Nasution (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the financial performance of PT Pegadaian (Persero) during the 2020–2024 period using financial ratio analysis. The financial ratios employed in this research include profitability ratios, liquidity ratios, and solvency ratios. This analysis is conducted to assess the company’s ability to generate profits and to fulfill both short-term and long-term financial obligations.The research method used is descriptive quantitative analysis. The data utilized are secondary data obtained from published financial statements, and the data collection technique is documentation. The data are then analyzed using descriptive analysis through financial ratio calculations. The results indicate that, in general, the financial performance of PT Pegadaian (Persero) experienced fairly positive development during the study period. Profitability ratios, particularly Return on Assets (ROA), show an increasing trend, indicating that the company’s ability to manage assets to generate profits has become more effective. However, several liquidity and solvency ratios still indicate conditions that require management attention to ensure a balanced relationship between assets, liabilities, and equity. Therefore, PT Pegadaian (Persero) needs to continuously improve financial management efficiency to achieve more optimal and sustainable performance in the future.